Perbandingan Perhitungan Angsuran KPR Konvensional dengan KPR Syariah - Peter . (Jurnal Manajemen Maranatha, 2008)
KPR is one of bank product which offering Debitur to get credit for buying a house. KPR has a different way to calculating the interest from credit which debitur had. Bank can calculate the interest with flat rate and effective rate, also now the bank give the new choice with KPR Syariah, so we can say that the regular KPR as KPR konvensional. All of that have one purpose that increase the credit distribution at KPR and make more options for new debitur. In the simulation we can see together that every result from every way to calculate the interest have own good and bad. We also can conclusion at the last, that KPR syariah is similar with KPR Konvensional if using flat rate for the credit which debitur get.